2013
DOI: 10.1016/j.bbr.2013.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Mozart effect, cognitive dissonance, and the pleasure of music

Abstract: We explore a possibility that the 'Mozart effect' points to a fundamental cognitive function of music. Would such an effect of music be due to the hedonicity, a fundamental dimension of mental experience? The present paper explores a recent hypothesis that music helps to tolerate cognitive dissonances and thus enabled accumulation of knowledge and human cultural evolution. We studied whether the influence of music is related to its hedonicity and whether pleasant or unpleasant music would influence scholarly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 38 publications
0
38
1
3
Order By: Relevance
“…[4] It has even been proposed that music may make people smarter! [5] The term "Mozart effect" has been coined to refl ect the proposed pleiotropic effect of music, which have not been entirely demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…[4] It has even been proposed that music may make people smarter! [5] The term "Mozart effect" has been coined to refl ect the proposed pleiotropic effect of music, which have not been entirely demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Musical emotions have been predicted to help overcoming emotional contradictions of cognitive dissonances among elements of knowledge and accumulate contradictory knowledge (Perlovsky, 2010, 2012a,b, 2014). These predictions have been experimentally confirmed (Masataka and Perlovsky, 2012, 2013; Perlovsky et al, 2013; Perlovsky, 2014). …”
Section: Aesthetic Emotionsmentioning
confidence: 60%
“…Existence of these specific emotions has been experimentally demonstrated and their cognitive functions have been analyzed (Perlovsky et al, 2010, 2013; Masataka and Perlovsky, 2012, 2013; Perlovsky, 2014). Musical emotions, an ability to be affected by sounds, the reason for evolutionary emergence of this ability were called “the greatest mystery” by Darwin (1871).…”
Section: Aesthetic Emotionsmentioning
confidence: 99%
“…Steps to demonstrating this experimentally have been made in (Masataka et al, 2012a(Masataka et al, , 2012b. It has been demonstrated that music helps resolve CD emotions of discomfort, so that contradictions in knowledge can be tolerated (Masataka et al, 2012a(Masataka et al, , 2012bPerlovsky, Cabanac et al, 2012). This made possible accumulation of knowledge and evolution of cultures.…”
Section: Resultsmentioning
confidence: 99%
“…This study followed a classical psychologic method that explored mental experience in interviews where participants answered printed questionnaires Balasko & Cabanac, 1998;Cabanac et al, 1997Cabanac et al, , 2002Cabanac & Bonniot-Cabanac, 2007;Ramirez et al, 2005Ramirez et al, , 2009Perlovsky, Bonniot-Cabanac et al, 2012). Thirty four anonymous participants (who were referred to by numbers only), 17 men (age 12 -70) and 17 women (age 16 -72) were presented two questionnaires each containing ten items.…”
Section: Experimental Methodsmentioning
confidence: 99%